Kuantan clay subgrade stabilization by using fly ash as stabilizer - Norazizan, Abd Rahim (2012)
Roadways and highway have a high potential for large volume use of fly ash stabilized soils. The main objective of this study is the utilization of fly ash to improve the subgrades material in highway construction. The study conducts various content of fly ash to the sample of clay soil collected along Kuantan - Pekan road. Compaction test and California Bearing Ration (CBR) test were conducted in the laboratory to determine the optimum mixture design. The sample were set up by mixing soil samples with various content of fly ash at different water content in compaction test to obtain optimum dry unit weight and optimum water content. The optimum water content were used in CBR tests of mixture of soil sample-fly ash. The performance analysis of fly ash stabilized soil should be based on laboratory test such as engineering properties of soil, compaction test and CBR test. The strength gain in stabilization is depend on two factors which is fly ash content and water content. The variation content of fly ash were 3%, 6%, and 9% by total weight. From the test, the fly as stabilization increased the CBR values for the mixture tested and has the potential to offer an alternative for clay soil subgrades improvement of highway construction.